Bisphenol F exposure induced vascular toxicity through intestinal microbiota imbalance - Yan, Jianlong; Pan, Yanbin; Liu, Huadong; Yuan, Jie; Chen, Jie; Gao, Yannan; Lin, Chaolan; Lin, Feng; Wang, Rongning; He, Yaqiong; Wang, Caiping; Xu, Cong; et al. (Frontiers in Microbiology, 2025)
IntroductionBisphenol F (BPF), a common substitute for bisphenol A (BPA), has documented toxicity in multiple organs, but its vascular effects remain unclear. This study investigated BPF’s role in vascular calcification (VC) and underlying mechanisms.MethodsDifferences in the intestinal microbiota were analyzed by 16S ribosomal RNA gene sequencing. Metabolites were analyzed using liquid chromatography-mass spectrometry. Faecal microbiota transplantation and antibiotic treatment experiments were performed to evaluate the functions of the intestinal microbiota in VC.ResultsWe enrolled consecutively 57 patients. Patients were assigned to a calcification group (30 patients) and a non-calcification group (27 patients) based on the presence or absence of calcification in the thoracic aorta wall. The results showed that patients with vascular calcification (VC) had higher levels of bisphenol F (BPF), bisphenol S (BPS) and bisphenol A (BPA) in the fecal samples than patients without VC. The thoracic aortic calcification score was significantly positively correlated with the BPF (Spearman r = 0.4935, p < 0.001), BPA (Spearman r = 0.2860, p < 0.05) and BPS (Spearman r = 0.2650, p < 0.05). We then explored the effects of BPF exposure on normal and vitamin D3 + nicotine (VDN)-treated rats. BPF exposure induced mild VC in normal rats and aggravated VC in VDN-treated rats. BPF exposure disturbed the gut microbiota and promoted inflammatory responses.ConclusionThe results here elucidate the mechanism underlying BPF-triggered or BPF-aggravated VC through the gut–vascular axis and provide a theoretical basis for cardiovascular disease risk assessment in humans.